The Effect of a 30-Meter Run on Physical Fitness Among Fifth-Grade Students at SDN 42 in Bengkulu City - Oktavia Sundari; Megi Personi; Asnawati Asnawati (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of 30-meter sprint training on improving the physical fitness levels of fifth-grade students at SDN 42 in Bengkulu City. The method used was a quantitative study with a pretest-posttest design, involving one group of subjects who received the intervention over 18 sessions. Data were collected through a sprint test, while data analysis utilized the Liliefors normality test, the test for homogeneity of variances, and the t-test at a 95% confidence level. The results showed that the students’ initial physical fitness levels before the intervention were generally in the “poor” and “moderate” categories; however, after the training, there was a significant improvement to the “good” and “very good” categories. The results of the statistical tests showed that the data were normally distributed and homogeneous, and the calculated t-value was smaller than the table t-value, so the research hypothesis was accepted. Based on these results, it was concluded that the 30-meter sprint training had a significant and effective influence on improving the physical fitness levels of fifth-grade students at SDN 42 in Bengkulu City.